(untitled) (Fiep Bulletin - online, 2014)
By adding into the curriculum of the course of Physical Education activities that fleeing the traditional sports, this work has as its main objective investigate the relations established between the experience of the activities of adventure and the excitement and emotions proportionate to the course of academic degree in Physical Education at the University Federal de Santa Maria. Based on the premise that problems can be solved and practices improved through observation, analysis and objective and complete descriptions, the collection of data is performed through analysis of photographs, interviews, questionnaires and observations. 46 scholars of both genders were involved in the UFSM Physical Education, aged from 17 to 36 years. The activities of outdoor adventure are increasingly known and widely used in various contexts, especially in the context of Physical Education and leisure. From categories Delight and Displeasure and after the completion of some procedures, canoeing, Rappelling and guidance had more pleasant answers, while the climbing had 86 notes of displeasure category and 84 descriptions of the category pleasure. The discovery of feelings and emotions through the experience of the activities of adventure on a graduates course in Physical Education confirms that implementation of these activities allows a life of self integration, with people, with nature and always seeks a balance in the relationship of coexistence; because the nature is part of our body and environment, transforming and allowing the body and spiritual culture being at the same time, personal and collective, giving space to a new human condition. All this makes it the new role of educators and teachers of Physical Education.